Updating Criminal Law in Civilized Law Enforcement and Social Justice - Murshal Senjaya (International Journal of Science and Society, 2021)
In essence, criminal law reform is a process of reviewing and reforming (reorienting and reforming) criminal law in accordance with the central principles of Indonesian societies socio-political, socio-philosophical, and socio-cultural values. Law enforcers can realize justice and a civilization that is not weak. This means that the aim of the Indonesian people is justice and a culture that is not passive. It needs straightening and vigorous law enforcement in irregularities because justice must be realized in everyday life.